EXPLORING THE CONCEPT OF ISLAMIC EDUCATIONAL MATERIALS AND MEDIA IN THE QUR'AN - Sari, Windy Dian; Sarnoto, Ahmad zain (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The Qur’an, as a guide for the lives of Muslims to live in this world until the hereafter, certainly provides discussions on education and needs to be explored and studied. Objective: This study examines the concept of Islamic educational materials and media in the Qur’an. Method: This type of research is educational research, using qualitative methods with a thematic exegesis (tafsir maudhu’i) approach. Data was collected from library sources. The collected data was analyzed using theories of educational materials and media. Research findings: First, the verses of the Qur’an tend to emphasize the value aspects of educational materials more than the technical details of the names of disciplines. In the Qur’an, Islamic educational materials include all kinds of knowledge that discuss humans and the universe. Second, the Qur’an and Western tradition agree in discussing the concept of educational media. Anything that can be used to improve the behavior of learners should be pursued. Conclusion: This research will be doubly useful: first, it will contribute to enriching the treasury of knowledge in Islamic Religious Education, and second, it will enrich the treasury of Qur'anic exegesis. Further research can confirm whether the verses of the Qur’an align with Western traditions or not; and in which aspects they align or do not; particularly regarding the topics of Islamic education materials and media